Factors influencing the motivation of maternal health workers in conflict setting of Mogadishu, Somalia. - Naima Said Sheikh; Abdi Gele (Public Library of Science (PLoS), 2023)
Motivated health workers play an important role in delivering high-quality maternal health services, especially in low-income countries where maternal mortality rates are high, and shortages of human resource for health is prevalent. The aim of this study is to investigate maternal health workers' motivation in three tertiary hospitals in Mogadishu Somalia. We used a semi-structured questionnaire that was validated and widely used in Sub-Saharan Africa to collect data from 220 health workers across three tertiary hospitals in Mogadishu between February and April 2020. Health worker motivation was measured using seven constructs: general motivation, burnout, job satisfaction, intrinsic job satisfaction, organizational commitment, conscientiousness, timeliness and attendance. A multiple linear regression analysis was performed to determine the predictors of health worker motivation. The results show that male health workers have a higher work motivation, with a mean score of 92.75 (SD 21.31) versus 90.43 (SD 21.61) in women. As regards to profession, significant correlation was found between health workers' motivation and being an assistant (coeff, 6.873, p = 0.001), nurse (coeff, 5.111, p = 0.000), physicians (coeff, 2.898 p = 0.042), pediatric assistants (coeff, 2.878, p = 0.048), midwife (coeff, 3.822, P = 0.01), and others (supervisor and pharmacist) (coeff, 5.623, P = 0.001). Unexpectedly, the gynecologists and midwives were the least motivated groups among the different professions, with mean scores of 83.63, (SD: 27.41) and 86.95 (SD: 21.08), respectively. Of the aforementioned seven motivation constructs, the highest mean motivation scores (from 1-5) were observed in conscientiousness and intrinsic job satisfaction. These results highlight the importance of targeted interventions that increase female health workers' motivation, particularly gynecologists and midwives. This can be done by providing non-financial incentives, in addition to encouraging their participation in the decision-making process. Further research is needed to investigate the effect of a lack of motivation among gynecologists and midwives on maternal health in Somalia.